Analisis Economic Value Added Untuk Mengukur Kinerja Keuangan PT. Federal Internasional Finance (Perusahaan Go Public Yang Terdaftar Pada Bursa Efek Indonesia) - Supriyanti; Bumi Kellen, Pius; Rahayu, Lustry (SUSTAINABLE, 2023)
ABSTRACT This study aims to assess the financial performance of PT. Federal Internasional Finance, a listed company on Indonesia Stock Exchange using the Economic Value Added method. The research was conducted from February to March 2023 using documentation data collection techniques in the form of published financial statements obtained through the Indonesia Stock Exchange, the official website of PT. Federal Internasional Finance and various literature related to research. The analysis was carried out using case study research with a quantitative descriptive approach. The focus of this research is on the financial statements of PT. Federal Internasional Finance for five years, from 2017 to 2021. The analysis technique used is the calculation of Economic Value Added which is calculated in three components, namely NOPAT, WACC and Invested Capital. The results of this study show that PT. Federal Internasional Finance is considered to have good financial performance, judging from the EVA value which shows a positive number. This situation can be interpreted to mean that PT. Federal Internasional Finance has succeeded in creating economic added value. Keywords: Financial report, Finansial performance, economic value added